Adaptability Evaluation and Selection of Improved tef Varieties in Growing Areas of Southern Ethiopia (Global Journal of Science Frontier Research, 2017)
Eight tef varieties including local checks were evaluated with the objective of selecting adaptable, best performing varieties and to assess farmers' criteria for tef variety selection during 2008 and 2009 cropping season at Areka and Hossana stations of Areka Agricultural Research center in the Southern region of Ethiopia. In the study the Tef varieties namely Koye, Gimbichu, Quncho, Dega tef, Keytena, Amarach and Ajora-1 were collected from the Federal and regional Research center along with local checks, Ethiopia and Regional Agricultural Research Institute. These materials were put into trial at Areka Agricultural Research center station farms at Areka and Hossana of Wolayta and Hadiya Zones. The trial was laid out in a randomized complete block design with three replications. Each plot measured 3m x 3m with 1m between plots and 1.5m between blocks. Sowing was done within the last week of July to 1 st week of August 2008 and 2009.
Keywords: Gimbichu; Quncho; Dega tef; Keytena